Emerging Trends in the Social and Behavioral Sciences 2016
DOI: 10.1002/9781118900772.etrds0395
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Perceived Chances and Risks Associated with Social Change

Abstract: Social change in the form of political transformation in the context of globalization and individualization is prevalent worldwide. Such change can occur gradually or abruptly and not always as part of people's conscious experience. In such situations, features of the broader ecological contexts in which people live moderate the process of coping. Successfully coping affects well‐being and other psychosocial outcomes and in most, but not all instances, requires active engagement, development of a sense of cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Consistent with Chen et al's (2010) study on Chinese parents of adolescents, we found that higher SES was related to more perceived opportunities and prospects and less work‐related risk and adversity among parents of preschool‐aged children. Macro‐level social change does not indiscriminately determine perceived demands and benefits associated with the social change at the individual level; rather, many factors function as filters in between (Silbereisen, 2016). Higher‐SES parents likely possess more material and nonmaterial resources, which can buffer the negative impact of social change on their work experiences, leading to decreased perceived risk in work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with Chen et al's (2010) study on Chinese parents of adolescents, we found that higher SES was related to more perceived opportunities and prospects and less work‐related risk and adversity among parents of preschool‐aged children. Macro‐level social change does not indiscriminately determine perceived demands and benefits associated with the social change at the individual level; rather, many factors function as filters in between (Silbereisen, 2016). Higher‐SES parents likely possess more material and nonmaterial resources, which can buffer the negative impact of social change on their work experiences, leading to decreased perceived risk in work.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors can affect how families perceive and act upon social change, such as available resources (e.g., social networks and cognitive abilities) and individual coping strategies (e.g., engagement or disengagement) (Pinquart & Silbereisen, 2004). For instance, high educational attainment is deemed an important individual resource that can often produce a more positive appraisal of and better coping with social change (Silbereisen, 2016). Kagitcibasi and Ataca's (2005) seminal work on Turkish childrearing showed that the utilitarian/material value of children was endorsed the most by rural parents and the least by urban high-SES parents, while urban low-SES parents fell in the middle.…”
Section: Social Change and Childrearingmentioning
confidence: 99%